Participating From the Comfort of Your Living Room: Feasibility of a Group Videoconferencing Intervention to Reduce Distress in Parents of Children With a Serious Illness or Injury. Issue 3 (2nd July 2016) - Rayner, Meredith; Dimovski, Anica; Muscara, Frank; Yamada, Jackie; Burke, Kylie; McCarthy, Maria; Hearps, Stephen J. C.; Anderson, Vicki A.; Coe, Amy; Hayes, Louise; Walser, Robyn; Nicholson, Jan M.
ABSTRACT: This study explored the feasibility and potential effectiveness of a videoconferencing group intervention for parents of children with a life-threatening illness. Parent functioning was assessed at pre, post, and 6-month follow-up (N = 13). Semistructured interviews explored parent experiences of the program and clinicians' experiences were systematically recorded. Attendance was high (92%) and parents reported comfort with the online delivery. Quantitative data revealed significant reductions on three of the nine measures examined (parent guilt/worry; unresolved sorrow/anger; lack of psychological flexibility). Clinician data are described and highlights the skills and program modifications required to adapt to the videoconferencing modality. A randomized controlled trial is now underway.